Edukasi Praktis Fiqih Feminin untuk Anak Perempuan Masa Pubertas dengan Media Buku Daily Haid di Desa Juwet - Saputra, Doni; Wildan Habibi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This study aims to improve the understanding of young girls in Desa Juwet, Kunjang District, Kediri Regency, about feminine fiqh, particularly concerning menstrual blood (haid) and istihadhah. The approach used in this research is Participatory Action Research (PAR), which actively involves the community in every phase, from identifying issues to implementing solutions. This educational program provides knowledge about purification practices, distinguishing different types of blood, and their influence on valid religious practices. The results of the study show that this program successfully raised awareness among young girls about the importance of maintaining cleanliness and purity according to Islamic teachings. Additionally, the application of feminine fiqh plays a role in strengthening their character and spirituality. The program received full support from local authorities and the community, and it had a positive impact on strengthening religious knowledge among young girls in the village. The success of this program highlights the importance of community involvement in the educational process and the need for strengthening the understanding of feminine fiqh at an early age to support better spiritual life.